Pharmacovigilance systems for safety monitoring of herbal medicines: assessment of the national regulatory authority, manufacturers and marketing authorisation holders in Tanzania - Alambo K. Mssusa; Lone Holst; Sheila Maregesi; Godeliver Kagashe (Journal of Pharmaceutical Policy and Practice)
Background The increase in the consumption of herbal medicines and their documented adverse reactions (ARs) necessitate countries to have good pharmacovigilance (PV) systems at all levels. PV systems should be frequently assessed in a systematic manner with available harmonised tools to monitor the implementation of efforts, strengthen the systems and identify areas for improvement.Objectives This study aimed to assess the performance of pharmacovigilance and its quality systems for monitoring herbal medicine safety at the National PV Centre at the Tanzania Medicines and Medical Devices Authority (TMDA), manufacturers and herbal medicine marketing authorisation holders (MAHs) to identify gaps, challenges and opportunities for improvement.Methods A descriptive cross-sectional study was conducted using structured interviews with key informants, questionnaires administered by the researchers and document analysis. A retrospective study of suspected ARs to herbal medicines received via the TMDA was also performed.Results Policies and a legal framework for regulatory control and safety monitoring of herbal medicines were in place with a well-established and functional PV system at the TMDA. However, some gaps and challenges in the safety monitoring of herbal medicines, such as underreporting, lack of training, and dissemination of PV information, have been identified. A total of 18 reports containing 40 suspected herbal medicine ARs were received at the TMDA. Among the MAHs, only 64% had PV systems, with only 29% having mechanisms for the collection of ARs from their products. Only a few MAHs (39%) had a qualified person in the PV. The majority of the MAHs (64%) had established a quality system for PV; however, the systems were inadequate.Conclusion Deliberate efforts need to be made to strengthen herbal medicine safety monitoring at the regulatory level. MAHs need to develop efficient PV systems and recruit qualified persons to identify safety issues related to herbal medicines.